Karakteristik Proksimat Tepung Daun Tarum (Indigofera zollingeriana) Hasil Fermentasi Aspergillus niger Perbandingan Air Berbeda Sebagai Bahan Baku Pakan - Panigoro, Novita; Ediwarman, Ediwarman; Fitria, Yuliana; Karim, Isnan Ibnu; Syahrizal, Syahrizal; Purnama, Padel (Universitas Batangahari Jambi, 2024)
This study aims to determine the nutritional content by proximate analysis of fermented tarum leaf meal (Indigofera zollineriana) as a raw material of fish feed. The method used in this research is the experimental method using Completely Randomized Design (CRD) with 4 treatments and 3 replicates. The factor studied were the comparison of tarum leaf meal with water which consisted of 4 treatment levels, namely A (tarum leaf meal and water 1:1 w/v), B (tarum leaf meal and water 1:2 w/v), and C (tarum leaf meal and water 1:3 w/v) with 0,3% of A, niger as bioactivator and K (tarum leaf meal) as control non fermented. The fermentation period was 6 days in aerobic condition with temperature at 35-40oC. From the above research, the proximate characteristic of fermented tarum leaf meal (I. zollineriana) has a different nutritional content for each factor. The best result was B (tarum leaf meal and water 1:2 m/v) with 40.09 ± 1.874% crude protein content, 11.24 ± 0.289% fat, 7.57 ± 1.845% crude fiber, 22.61 ± 0.177% ash content, and 18,47 ± 2,347% NNFE (non nitrogen free extract).